STRATEGI KOMUNIKASI PEMASARAN PT. OPPO INDONESIA DALAM MENINGKATKAN CITRA SMARTPHONE OPPO - Windo Chandra Siahaan; Yan Hendra; Armansyah Matondang (Universitas Medan Area, 2017)
Background of this research by sales information smartphone OPPO Year 2017. According to IDC (International Data Corporation) with counterpoint.com, smartphone OPPO was ranked as the second smartphone best-selling in Indonesia, a phenomenon that a major reason researchers. The purpose of this study to determine how the marketing communication strategy PT. INDONESIA OPPO in improving the smartphone OPPO image, and the contributing factorsimage smartphone OPPO is not significantly increased. Researchers used Promotion Mix theory is supported by Diffusion of Innovations. The method I use in this research is descriptive qualitative. Researchers chose Trainer smartphone OPPO as a key informant, and supported by five additional informants to strengthen the validity of a study. The results of the present study, researchers found that the tagline